2d-4(d+6)=6d-48

Simple and best practice solution for 2d-4(d+6)=6d-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2d-4(d+6)=6d-48 equation:


Simplifying
2d + -4(d + 6) = 6d + -48

Reorder the terms:
2d + -4(6 + d) = 6d + -48
2d + (6 * -4 + d * -4) = 6d + -48
2d + (-24 + -4d) = 6d + -48

Reorder the terms:
-24 + 2d + -4d = 6d + -48

Combine like terms: 2d + -4d = -2d
-24 + -2d = 6d + -48

Reorder the terms:
-24 + -2d = -48 + 6d

Solving
-24 + -2d = -48 + 6d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-6d' to each side of the equation.
-24 + -2d + -6d = -48 + 6d + -6d

Combine like terms: -2d + -6d = -8d
-24 + -8d = -48 + 6d + -6d

Combine like terms: 6d + -6d = 0
-24 + -8d = -48 + 0
-24 + -8d = -48

Add '24' to each side of the equation.
-24 + 24 + -8d = -48 + 24

Combine like terms: -24 + 24 = 0
0 + -8d = -48 + 24
-8d = -48 + 24

Combine like terms: -48 + 24 = -24
-8d = -24

Divide each side by '-8'.
d = 3

Simplifying
d = 3

See similar equations:

| (5a^2b-^3/10a-^2b-^4)^3 | | z/5-4=3/1/3 | | .15x+20=.10x+30 | | .10x+.25y=5.10 | | 9x18/5 | | 9.2x+50.82=-10.8x+50.10 | | (5a^2b-^3)/(10a-^2b-^4)^3 | | 9x+3=65 | | K+(4K+32)=32 | | 20-x/15=17 | | 4(2x-8)+6=26 | | 250000=5000{[(1.12)^n-1]/[.12]} | | 5w+10=15w | | 57x=45 | | 4(w-16)+2w=0 | | 4x=9x-9 | | 4m-7=1 | | 4x+ef=9x-9 | | 10p-4= | | 7(5/9)-9=4-2(5/9) | | 5(2m+9)=10(m+3)-40m | | -7t+2=16 | | 3.5d+9.75=6+4.75d | | n/-3=-16/3 | | 3-3r+5r=2r+2 | | z/5-7=1/5/6 | | N/6×6/1 | | -7.6(x-3.25)=30.4 | | 1+(4+a)=15 | | 3.6=7x | | 4+49x=28x+22 | | 12=-4(-6g-3) |

Equations solver categories